The efficacy of onabotulinumtoxinA in patients with previous failed augmentation cystoplasty: Cohort series and literature review. Issue 6 (22nd June 2020) - Toia, Bogdan; Pakzad, Mahreen H.; Hamid, Rizwan; Wood, Dan N; Greenwell, Tamsin J.; Ockrim, Jeremy L.
Abstract: Aims: To investigate the role of onabotulinumtoxinA (BTX‐A) injections in patients with failed augmentation cystoplasty for neuropathic or idiopathic detrusor overactivity (NDO or IDO). Methods: A retrospective review of all cystoplasty patients who underwent onabotulinumtoxinA injection at a tertiary center between 2008 and 2019 was performed. Details including indications and time from cystoplasty, video‐urodynamic parameters, onabotulinumtoxinA dose, and clinical outcomes were analyzed. Telephone interview was performed for patients that requested repeat onabotulinumtoxinA injections. The interview included a modified PGIC7 and UDI6 questionnaires. A positive clinical response was considered improvement of overactive symptoms sufficient to merit repeat onabotulinumtoxinA injection and a modified PGIC7 of four or above. Results: Thirty patients were identified (11 men and 19 women). The indications for augmentation were IDO (n = 18) or NDO (n = 12). Mean age at the time of cystoplasty was 42 years (range, 10‐61). Interval between cystoplasty and initial onabotulinumtoxinA was 98 months (range, 3‐271). Video‐urodynamics before onabotulinumtoxinA revealed low compliance in 13 patients, DO in 22 patients, and combined low compliance/DO in 10. The median maximum cystometric bladder capacity was 338 mL (range, 77‐570 mL). Thirteen patients responded to onabotulinumtoxinA injections. Higher peak DO pressure was associated with a significantly higher chance that the patient would experience benefit from the injections P  = .026). The patients that responded to onabotulinumtoxin A underwent a total of 115 procedures (mean, 8.8 injections) over a mean 88 months (range, 20‐157 months). Conclusions: Forty‐three percent of patients responded well to intra‐detrusor onabotulinumtoxinA injections. This avoided the need for more invasive surgery and had a positive impact on their quality of life.